Field notes contributed by Thomas H. Kent, fall 1984 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1984)
Field notes were contributed by Thomas H. Kent, fall 1984. Fifty-nine bird species were sighted with eight other observers, mostly in Johnson County. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed